A Study of Cross-Border Shopping: Why Inhabitants of St Petersburg Prefer to Do Shopping in Finland? - Ольга Юрьевна Гурова (Journal of Economic Sociology, 2012)
The paper discusses cross-border shopping considering it as a practice of shopping outside one’s country of residence. The article is focused on the shopping practices of St Petersburg residents visiting the capital of Finland. The popularity of cross-border shopping has been increasing over in Russia as it became a part of the middle-class lifestyle. Drawing on the data from qualitative interviews, author discusses a set of reasons stimulating and restraining cross-border shopping.